2018
DOI: 10.1039/c8qi00251g
|View full text |Cite
|
Sign up to set email alerts
|

One-step CVD fabrication and optoelectronic properties of SnS2/SnS vertical heterostructures

Abstract: A high-quality vertical SnS2/SnS heterostructure with excellent photoresponse has been fabricated and demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 50 publications
2
25
0
Order By: Relevance
“…1a). Note that this geometry is the inverse of previously reported SnS 2 /SnS vertical heterostructures 35 . Selected-area low-energy electron diffraction (micro-LEED) was used to analyze the crystal structure and lattice registry.…”
Section: Resultssupporting
confidence: 59%
“…1a). Note that this geometry is the inverse of previously reported SnS 2 /SnS vertical heterostructures 35 . Selected-area low-energy electron diffraction (micro-LEED) was used to analyze the crystal structure and lattice registry.…”
Section: Resultssupporting
confidence: 59%
“…SnS 2 ‐based optoelectronics devices have shown a remarkable performance over the years. [ 11,23–25 ] However, SnS 2 has sulfur deficiency/vacancies as its intrinsic defects, which could potentially influence its optoelectronic performance. Nonetheless, it has been reported that these intrinsic defects have hindered its optical absorption and caused Fermi level pinning effect, which results in substantial metal contact resistance, thus preventing it from achieving its full potential performance in optoelectronic device applications.…”
Section: Introductionmentioning
confidence: 99%
“…[36,173,203] Moreover, the abundant constituent elements, excellent stability, and low toxicity compared to lead and cadmium, also make SnSbased nanostructures more promising than most other semiconductors on the basis of long-term, low-cost, and environmentally benign optoelectronic technologies. [23,25,60,78,87,103,139,[210][211][212][213][214][215] In 2020, Krishnamurthi et al [23] successfully fabricated single-layer and multilayer SnS with lateral dimensions reaching the millimeter scale by utilizing van del Waals transfer of molten Sn on conventional substrates, such as SiO 2 /Si. Figure 21a presents the schematic diagram of SnS NS-based photodetector fabricated on a SiO 2 /Si substrate.…”
Section: Optoelectronicsmentioning
confidence: 99%